A prospective observational to study sociodemographic profile, clinical profile and pattern of gynecological malignancies in a tertiary care center in Himachal Pradesh - Ravindran, Ashritha; Sood, Rajeev; Negi, Kalpna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cancer is the second leading cause of death globally and is estimated to account for 9.6 million deaths in 2018. Due to the lack of cancer awareness, variable pathology, and dearth of proper screening facilities in developing countries such as India, most women report at advanced stages, adversely affecting the prognosis and clinical outcomes. The aim of the study was to study the sociodemographic profile, clinical profile, pattern of gynaecology malignancies and their histopathological findings of all gynaecological malignancy patients attending gynaecological OPD. Methods: A prospective observational study was conducted in the Department of OBG, KNH Shimla from June 2019 to May 2020 where 241 gynaecological malignancy patients were recruited. Detailed history, general physical examination, systemic, gynaecological examination and required investigation was done and the data was analysed. Results: The most commonly occurring gynaecological malignancy was cervical cancer. 82.2% of the patients belonged to the age group 40-69 years. Majority of the patients were multiparous, belonged to rural background, belonged to Hindu community. 69.3% were menopausal. Among the 132 women who gave history of age at first coitus as less than 18 years, 60.6% of them had cervical cancer. Most common presenting complaints was post-menopausal bleeding. In cervical cancer 43.6% of patients diagnosed at stage III and were managed by radiation therapy. Conclusions: According to this study, cervical cancer is the most common gynaecological malignancy followed by ovarian cancer. Most of these patients seeked medical attention in advanced stage.